2009
DOI: 10.1037/a0015076
|View full text |Cite
|
Sign up to set email alerts
|

Authoritative parenting among immigrant Chinese mothers of preschoolers.

Abstract: The goals of this study were: (a) to examine authoritative parenting style among Chinese immigrant mothers of young children, (b) to test the mediational mechanism between authoritative parenting style and children’s outcomes; and (c) to evaluate 3 predictors of authoritative parenting style (psychological well-being, perceived support in the parenting role, parenting stress). Participants included 85 Chinese immigrant mothers and their preschool children. Mothers reported on their parenting style, psychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 77 publications
9
76
1
8
Order By: Relevance
“…Within the dearth of research examining the parenting of Chinese immigrants, the results have been mixed. For instance, while Gorman (1998) found that Chinese immigrant parents applied authoritarian parenting, Cheah, Leung, Tahseen, and Schultz (2009) reported that Chinese immigrant mothers strongly espoused authoritative parenting. Considering together, the scarcity of research devoted to examining the parenting of Chinese immigrants in the USA and the incongruent findings concerning the parenting styles among this population leave this area in need of more investigation.…”
Section: The Important Role Of Parenting In Child Outcomesmentioning
confidence: 97%
“…Within the dearth of research examining the parenting of Chinese immigrants, the results have been mixed. For instance, while Gorman (1998) found that Chinese immigrant parents applied authoritarian parenting, Cheah, Leung, Tahseen, and Schultz (2009) reported that Chinese immigrant mothers strongly espoused authoritative parenting. Considering together, the scarcity of research devoted to examining the parenting of Chinese immigrants in the USA and the incongruent findings concerning the parenting styles among this population leave this area in need of more investigation.…”
Section: The Important Role Of Parenting In Child Outcomesmentioning
confidence: 97%
“…Kohlberg, 1984;Piaget, 1932Piaget, /1965. Children under six years of age are considered to be incapable of making moral judgement in the Chinese society, and therefore not punished for misbehaviour (Cheah, Leung, Tahseen, & Schultz, 2009). This may explain why most children did not refer to fear of punishment or the authority in their moral judgements.…”
Section: Maintaining Harmony or Upholding Personal Right?mentioning
confidence: 99%
“…Researchers claim that the authoritative parenting style described by Baumrind or the democratic parenting style as proposed in the Individual Psychology literature appears to be more acceptable based on research ndings that show higher levels of empathy, pro-social behavior, life satisfaction, co-operative attitudes and lower depression in children (Evans, 2005;Hubbs-Tait, Kenedy, Page, Topham & Harrist, 2008;McGillicuddy-De Lisi & De Lisi, 2007;Milevsky, Schlechter, Netter & Keehn, 2007;Latouf, 2008;Cheah, Leung, Tahseen & Schultz, 2009;Pong, Johnston & Chen, 2010). Many of these ndings support the clinical and psycho-educational materials based on the Individual Psychology principle represented in the parenting programs such as Systematic Training of E ective Parenting (Dinkmeyer Sr. et al, 1997) and Active Parenting (Popkin, 1993).…”
Section: Research On Baumrind's Parenting Styles Modelmentioning
confidence: 99%